Day 2 Wed, October 16, 2019 2019
DOI: 10.2118/196589-ms
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Diffusion Coefficients of Shale Oil, Gas, and Condensate with Nano-Confinement Effect

Abstract: Molecular diffusion plays an important role in oil and gas migration and transport in tight shale formations. However, there are insufficient reference data in the literature to specify the diffusion coefficients within a porous media. This study aims at calculating diffusion coefficients of shale gas, shale condensate, and shale oil at reservoir conditions with CO2 injection for EOR/EGR. The large nano-confinement effects including large gas-oil capillary pressure and critical property shifts on diffusion coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…They concluded that the Hayduk and Minhas correlation [16] agrees well with the experimental data. Du and Nojabaei [17] investigated different diffusion coefficient correlations and concluded that the Sigmund correlation [14] shows the closest match to the experimental data.…”
Section: Introductionmentioning
confidence: 90%
“…They concluded that the Hayduk and Minhas correlation [16] agrees well with the experimental data. Du and Nojabaei [17] investigated different diffusion coefficient correlations and concluded that the Sigmund correlation [14] shows the closest match to the experimental data.…”
Section: Introductionmentioning
confidence: 90%
“…where M ik is the molecular weight of solvent; µ k is the viscosity of phase k; and v bi is the partial molar volume of component i at the boiling point. It should be noted that Wilke-Chang (1955) correlation was developed for low-pressure liquid systems and a recent study indicated that the application of Wilke-Chang correlation is not suitable for high-pressure shale fluids [41]. A more generalized diffusion correlation was developed by Leahy-Dios and Firoozabadi (2007), which is capable of estimating the diffusivities of gas, liquid, and supercritical states of nonpolar binary or multicomponent mixtures at a wide pressure and temperature range [42].…”
Section: Sensitivity Analysismentioning
confidence: 99%